Greensplaining environmental justice: A narrative of race, ethnicity, and justice in urban greenspace development. (3rd July 2021) - Fernandez, Mariela; Harris, Brandon; Rose, Jeff
ABSTRACT: While urban greenspaces play an important role in shaping the cultural and social dimensions of cities, these spaces are also inherently political, often serving to perpetuate the exclusion and subordination of racially marginalized populations. Drawing upon critical race theory, the purpose of this research is to use narratives to highlight how race, structural racism, White privilege, and power continue to shape environmental injustices in the urban landscape. By sharing these stories, we illustrate how (a) environmental injustices stemming from structural and overt racism are often positioned as ordinary experiences, (b) the racialized state continues to foster environmental injustices in Latinx communities, and (c) how techniques of what we refer to as "greensplaining" are deployed by environmentalists and conservationists as further justification for White privilege, racialized marginalization, and processes of gentrification.